2023
DOI: 10.1111/jipb.13545
|View full text |Cite
|
Sign up to set email alerts
|

Climate factors affect forest biomass allocation by altering soil nutrient availability and leaf traits

Hede Gong,
Wenchen Song,
Jiangfeng Wang
et al.

Abstract: Biomass in forests sequesters substantial amounts of carbon; although the contribution of aboveground biomass has been extensively studied, the contribution of belowground biomass remains understudied. Investigating the forest biomass allocation is crucial for understanding the impacts of global change on carbon allocation and cycling. Moreover, the question of how climate factors affect biomass allocation in natural and planted forests remains unresolved. Here, we addressed this question by collecting data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…Numerous studies have shown that plant life type, functional traits, climate, soil nutrients, and local NPP collectively affect the allocation of plant aboveground and belowground biomass [11,23,45]. To adapt to changing environmental conditions, plants adjust their morphological traits to obtain more resources, ultimately resulting in biomass accumulation [20,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that plant life type, functional traits, climate, soil nutrients, and local NPP collectively affect the allocation of plant aboveground and belowground biomass [11,23,45]. To adapt to changing environmental conditions, plants adjust their morphological traits to obtain more resources, ultimately resulting in biomass accumulation [20,34].…”
Section: Discussionmentioning
confidence: 99%
“…Optimal allocation theory suggests that in nutrient-poor soil environments, plants allocate more biomass to the roots than the aboveground parts [22]. As soil fertility increases, the proportion of biomass allocated to the aboveground parts of plants will significantly increase [23]. Previous research has found that adding N and P to nutrient-poor soil environments weakens the competition between root systems and soil microorganisms due to higher soil N content [24].…”
Section: Introductionmentioning
confidence: 99%
“…The N/P ratio reflects plant demand for nitrogen and phosphorus ( Tessier and Raynal, 2003 ) and plays an important role in investigating plant competition, ecosystem nutrient cycling, and ecosystem stability ( Xu et al., 2020 ). Numerous studies have shown that abiotic factors such as climate change and soil nutrients play a key role in shaping the spatial variability of forest leaf nutrients ( Gong et al., 2023 ). However, studies also indicate that stand factors like forest age play a significant role as well ( Nielsen et al., 2019 ), and it remains unknown whether different forest origins (planted forest, natural forest) affect leaf nutrient functional traits.…”
Section: Introductionmentioning
confidence: 99%
“…Higher temperatures and abundant rainfall largely alleviate environmental survival stress for trees, leading them to allocate more resources to compete for light. They increase specific leaf area (SLA) to enhance photosynthetic capacity and effectively utilize light resources [ 10 , 11 ]. Conversely, in cold and arid conditions, the survival stress of trees increases, forcing them to devote more resources to survival.…”
Section: Introductionmentioning
confidence: 99%
“…Trees with high SLA and low LDMC typically adopt a fast investment–return strategy to better adapt to nutrient-rich soil conditions. Under conditions of high nitrogen and phosphorus, trees often increase leaf area (higher SLA) and reduce the proportion of leaf dry weight to enhance photosynthetic efficiency, optimizing their growth and development, minimizing nutrient investment in support structures and durability, and investing more nitrogen and phosphorus to support leaf growth [ 11 ]. In environments with low nitrogen and phosphorus, trees conserve more nutrients in longer-lived and more resilient tissues, adopting a conservative resource utilization strategy to adapt to these conditions [ 18 ].…”
Section: Introductionmentioning
confidence: 99%